Mouthwash use and cancer of the head and neck: a pooled analysis from the International Head and Neck Cancer Epidemiology Consortium. Issue 4 (July 2016) - Boffetta, Paolo; Hayes, Richard B.; Sartori, Samantha; Lee, Yuan-Chin A.; Muscat, Joshua; Olshan, Andrew; Winn, Deborah M.; Castellsagué, Xavier; Zhang, Zuo-Feng; Morgenstern, Hal; Chen, Chu; Schwartz, Stephen M.; et al.
Abstract : Most mouthwashes contain alcohol, a known cause of head and neck cancer (oral cavity, pharynx, larynx), likely through the carcinogenic activity of acetaldehyde, formed in the oral cavity from alcohol. We carried out a pooled analysis of 8981 cases of head and neck cancer and 10 090 controls from 12 case–control studies with comparable information on mouthwash use in the International Head and Neck Cancer Epidemiology Consortium. Logistic regression was used to assess the association of mouthwash use with cancers of the oral cavity, oropharynx, hypopharynx, and larynx, adjusting for study, age, sex, pack-years of tobacco smoking, number of alcoholic drinks/day, and education. Compared with never users of mouthwash, the odds ratio (OR) of all head and neck cancers was 1.01 [95% confidence interval (CI): 0.94–1.08] for ever users, based on 12 studies. The corresponding ORs of cancer of the oral cavity and oropharynx were 1.11 (95% CI: 1.00–1.23) and 1.28 (95% CI: 1.06–1.56), respectively. OR for all head and neck cancer was 1.15 (95% CI: 1.01–1.30) for use for more than 35 years, based on seven studies ( P for linear trend=0.01), and OR 1.31 (95% CI: 1.09–1.58) for use more than one per day, based on five studies ( P for linear trend <0.001). Although limited by the retrospective nature of the study and the limited ability to assess risks of mouthwash use in nonusers of tobacco and alcohol, this large investigation shows potential risks for head and neck cancer subsites and in long-term and frequent users of mouthwash. This pooled analysis provides the most precise estimate of the association between mouthwash use and head and neck cancer. Abstract : Supplemental Digital Content is available in the text.